The Effect of garlic extract, hybridization, seedling age, and foliar application on the growth characteristics and yield of broccoli plants - Mohammed younus hraiga; Nawal Mahdi Hammood (University of Thi-Qar Journal of agricultural research, 2024)
belonging to the Agricultural Research Station at the College of Agriculture, University of Basra, Karima Ali. The aim of the study was to investigate the impact of two hybrids (Matsuri and 2004), three seedling ages (30, 45, and 60 days), and five concentrations of garlic water extract (10, 20 mL L-1 of local garlic variety and 10, 20 mL L-1 of Chinese garlic variety), with a control treatment (0). There were a total of 30 experimental treatments conducted as a split-plot design with two replications using a complete randomized block design.Matsuri hybrid exhibited significant superiority over the 2004 hybrid in leaf area, leaf count, lateral shoot weight, lateral shoot diameter, and lateral shoot count for both seasons. Moreover, the 30-day-old seedlings showed significant superiority over the other ages in all studied traits for both seasons. Additionally, the treatment with 20 mL L-1 of Chinese garlic extract significantly outperformed the other spray concentrations for both seasons. Some pairwise interactions had significant effects on the study traits, while others were not significant.